Pembinaan Karakter Percaya Diri dalam Berdakwah Terhadap Santri di Pesantren Arafah Sungaipenuh - Farta Akhnuari, Dika; Zuhdi, Ahmad (Journal of Da'wah, 2023)
This research was purpossed by the results of prelimary observations who was done on 04-05 August 2022 at the Arafah Sungai Penuh Islamic boarding school. From the prelemiray observation it was found that there were several students who were not confident in the field of da'wah. This is indicated by the lack of students who appear to give lectures in various activities such as commemorating Maulid Nabi, Isra' Mi'raj and etc. This reserch was used a qualitative method using primary data sources, such as: teachers, students and headmaster. The data was collected by using observation, interviews, and documentation. The results of the research indicated that, the teacher made the muhadharah program three times a week and trains students to perform in extracurricular activities and the teacher plays important role in fostering students' self-confidence by guidance, instilling religious knowledge, motivation and discipline of them. The strategy for building self-confidence in preaching to students at the Arafah Sungai Penuh Islamic Boarding School is by engraft religious knowledge, positive thoughts, positive attitudes and directly speaking in front of classmates and always setting an example for good preaching to students. The obstacle was faced by the teacher in fostering the character of students' self-confidence was the students do not have to appear preaching. Eventhough, they have memorized the concept and the strategy of preaching, besides that, it is difficult for students to gain confidence because they are afraid of being wrong when performing